A RISK FACTOR STUDY OF VISUAL ACUITY IN PTERYGIUM PATIENTS ON BAWEAN ISLAND, INDONESIA, 2023 - Handayani, Rizki Matta; Jelita, Erdina Hana; Handayani, Rizki Matta; Kaptuti, Ujik Unari Dwi; Anandita, Faizal Ablansah (Ophthalmologica Indonesiana, 2024)
Introduction & Objectives Pterygium is associated with excessive exposure to sunlight and UV rays in the eyes. This causes island countries in Asia which are in the "pterygium belt", including Indonesia, to have a high prevalence of pterygium. Other risk factors, such as gender, age, and medical conditions, such as blood pressure and diabetes, have also been linked to this chronic eye disease. However, of the many studies that have examined pterygium and its risk factors, very few have linked these risk factors to the severity or grade of the pterygium. This study aimed to study the correlation between pterygium severity and its risk factors, within the people of Bawean Island, Indonesia. Methods This research was an analytic cross-sectional, with the research sample selected by total sampling method based on the results of a diagnosis performed by ophthalmologists. The research variable were visual acuity (good-blindness), the severity / grade of pterygium (I-IV), gender, age, occupational group, pterygium location, blood pressure, and fasting blood sugar. Results From 62 patients with pterygium, 75,8% categorized as grade IV, and 41,93% has a moderate to blindness visual acuity. More than half of the patients are old female above 50 years old with 40,32% has an occupational risk of sunlight exposure. Conclusion The results of this study indicate that although all the risk factors studied did not have a significanty on the visual acuity, age (p=0,13) and occupational groups (p=0,20) are determinant factors on the visual acuity of pterygium patients on Bawean Island, Indonesia.